1974
DOI: 10.1136/ard.33.2.140
|View full text |Cite
|
Sign up to set email alerts
|

Articular and cutaneous manifestations of gonorrhoea. Review of sixteen cases.

Abstract: The incidence of gonococcal infection of the urogenital tract has risen steeply throughout the world in the past few years. With this rise has re-emerged a benign syndrome of gonorrhoea associated with acute polyarthritis and characteristic vesiculopustular skin lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1974
1974
2004
2004

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Past studies have reported variable sensitivities of these ancillary tests for septic arthritis. The sensitivity of an elevated WBC ranges from 19% to 77%, 2,[4][5][6][7][8][13][14][15][16][17][18][19]21,[25][26][27]33 the sensitivity of an elevated ESR ranges from 71% to 94%, [2][3][4][5][6][7][8]14,15,[17][18][19][20][21]30,[33][34][35] and the sensitivity of a jWBC greater than 50,000 cells/mm 3 ranges from 0% to 92%. 1,3,[17][18][19]21,[25][26][27][28][29][30]33,36,…”
Section: Discussionmentioning
confidence: 99%
“…Past studies have reported variable sensitivities of these ancillary tests for septic arthritis. The sensitivity of an elevated WBC ranges from 19% to 77%, 2,[4][5][6][7][8][13][14][15][16][17][18][19]21,[25][26][27]33 the sensitivity of an elevated ESR ranges from 71% to 94%, [2][3][4][5][6][7][8]14,15,[17][18][19][20][21]30,[33][34][35] and the sensitivity of a jWBC greater than 50,000 cells/mm 3 ranges from 0% to 92%. 1,3,[17][18][19]21,[25][26][27][28][29][30]33,36,…”
Section: Discussionmentioning
confidence: 99%
“…Past studies have reported variable sensitivities of these ancillary tests for septic arthritis. The sensitivity of an elevated WBC ranges from 19% to 77%, 2,4-8,13-19,21,25-27,33 the sensitivity of an elevated ESR ranges from 71% to 94%, [2][3][4][5][6][7][8]14,15,[17][18][19][20][21]30,[33][34][35] and the sensitivity of a jWBC greater than 50,000 cells/mm 3 ranges from 0% to 92%. 1,3,[17][18][19]21,[25][26][27][28][29][30]33,36,37 Much of the literature consists of case series studies like ours, often with variable values for normal WBC, ESR, and jWBC.…”
Section: Discussionmentioning
confidence: 99%
“…Seifert et al, 13 reporting a series of cases of gonococcal arthritis, noted that they presented not to the venereologist but to the general physician, rheumatologist or dermatologist. Typically there was a mild febrile illness about 2 weeks after exposure with the involvement of multiple joints and absence of leucocytosis making it easy to overlook the possibility of an infective aetiology.…”
Section: Infectionsmentioning
confidence: 97%